Quantitative benthic distribution in Kislo-Sladkoye Lake ... - Malyshko, Ekaterina; Nesmeyanova, Elena; Ilchenko, Stella; Volovich, Nadezhda; Mardashova, Maria; Krasnova, Elena; Menshenina, Larisa (EARSeL eProceedings, 2015)
Water bodies separating from the sea have recently been an object of increasing interest among specialists in various fields. Kislo-Sladkoye Lake situated near the White Sea Biological Station of Moscow State University is one of the model separating water reservoirs. The lake is under monitoring for hydrological, hydrochemical, and microbiological characteristics. Bacterial and phytoplankton communities are also a focus of attention. However, some aspects are still poorly understood. In this work first results of a quantitative survey of macrobenthos are presented. The work is dedicated to the quantitative evaluation of the macrobenthic community of Kislo-Sladkoye Lake. Thirty samples were taken from 16 stations at the following depths: 0.5, 1, 1.5, 2, 2.5, 3, 4 m. Ten species of macrobenthic invertebrates were found in the dredge samples: Insecta: Diptera - 4 taxa (larvae and adults); Mollusca: Gastropoda - 2 taxa; Oligochaeta - 1 taxon, there were also Nematoda, Chironomidae as well as houses of ...